The initiative of stem schools in Egypt: Issues of process, teachers' compatibility and governance - AbdelMeguid, Lamis (AUC Knowledge Fountain, 2018)
This study discusses the Science, Technology, Engineering, and Mathematics (STEM) initiative as the latest policy move undertaken by the Egyptian government to improve the education system and prepare future generations of professionals in these fields. The findings of this study are based on a case study of two schools in Egypt. Data was collected using face-to-face and focus group interviewing along with a review of documents. This thesis discusses the role of the different stakeholders, the program structure, the student and teacher selection processes, teaching techniques, curricula, assessments, sustainability plan, and the views of STEM graduates. The study highlights the positive STEM learning environment but identifies a number of issues that could be threatening the quality and continuity of the STEM initiative in Egypt. These relate to: (1) the complex overarching bureaucratic legislation structure; (2) challenges in curricula design and assessment criteria; (3) teachers' training and system compatibility challenges; and most importantly, (4) the shortfall in the availability of sustainable funding. Relying on the findings of the global STEM experience, the study discusses international best practices and recommendations.